The dynamics of Thailand's real exchange rate - Abdul Hamid, Baharom; Habibullah, Muzafar Shah; Mohamed, Azali; Chow, Li Shen (Institute of Interdisciplinary Business Research, 2011)
This study examines the fundamental determinants of the real exchange rate in Thailand during the period of 1976-2006, using the Bounds testing approach suggested by Pesaran et al. (2001). Three main fundamentals are used to identify the RER, namely, the productivity differentials (proxied by GDP per capita), the net foreign assets position (proxied by the current account balance, CAB), and the real interest rate differential (RIR). The empirical results demonstrate stable long run relationship between the real exchange rate (RER) and GDP per capita (GDPPC), real interest rate (RIR) and current account balance (CAB).